Beckwith-Wiedemann syndrome in a child with chromosome 18q deletion. Issue 2 (February 1998) - Brewer, C M; Lam, W W; Hayward, C; Grace, E; Maher, E R; FitzPatrick, D R
Abstract : Molecular genetic investigation of a female infant with Beckwith-Wiedemann syndrome (BWS) showed loss of IGF2 imprinting but no evidence of uniparental disomy. In addition, a deletion of chromosome 18q22.1 was identified in this infant without clinical features of 18q-syndrome (microcephaly, short stature, hypotonia). The association of a chromosome 18 deletion and BWS may be coincidental or may indicate the location of a trans activating regulator element for maintenance of IGF2 imprinting.